The Cultural Meaning of Tebolak and Women's Agency in Preserving Collective Memory in Kabar Village, East Lombok - Nur Laili Hidayah (Jurnal Sosial dan Humaniora, 2026)
This ethnographic research  aims to explore the significance of tebolak culture, the traditional Sasak food cover craft, and to identify female agents in preserving the collective memory of the community in Kabar Village, East Lombok. Data were collected through participant observations, in-depth interviews with cross-generational women artisans, and documentation. The results of the study show that the significance of tebolak culture is manifested in every motif, color, and process of its making, which reflects the harmony of life, local cosmology, and social ethics of the Sasak people. Furthermore, this study reveals how women occupy a central position as the main actor (agent) in the transmission of cultural knowledge. In the midst of modernization and the onslaught of mass-produced products, the women in this artisan family are involved in a silent resistance to maintain the existence of tebolak. Through the process of weaving and weaving passed down from mother to daughter, they not only support the family household economy but also act as guardians of collective memory, connecting past generations with the present. This study concludes that the preservation of tebolak in Kabar Village is highly dependent on the resilience of Sasak women, which simultaneously integrate domestic, economic, and cultural roles